Selectively facilitating the electron acceptance of methanogens by riboflavin. (August 2022) - Liu, Fanghua; Zheng, Shiling; Wang, Bingchen; Zhang, Xiaoli
Abstract: Direct interspecies electron transfer systems of acetoclastic and hydrogenotrophic methanogens with Geobacter metallireducens have been successfully established. However, the effects of riboflavin (RF) on these cocultures are not yet known. This study established two syntrophic cocultures with RF, acetoclastic Methanosarcina mazei and hydrogenotrophic Methanobacterium sp. YSL with G. metallireducens, and compared their transcriptome profiles. The results showed that a shorter start-up time lag of Methanobacterium sp. YSL was accompanied by unique transcriptome profiles when RF was added. Furthermore, the differential expression of key genes involved in the pathways was analyzed by comparative transcriptomics. Different proposed methanogenic pathways in the coculture systems were activated by M . mazei and Methanobacterium sp. YSL with RF. The earlier start-up of Methanobacterium sp. YSL cocultures was closely related to the overexpression of the gene encoding methyl-coenzyme M reductase (Mcr II) initiated by RF. The results revealed the distinct transcriptome profiles of acetoclastic and hydrogenotrophic methanogens accepting electrons from Geobacter mediated by RF, indicating the selective facilitation of the electron acceptance of methanogens and shedding new light on the fast start-up of anaerobic digesters for wastewater treatment.